Android Based Educational Game Application To Introduce Cultureand Tribes In West Sulawesi - Muzdalifah, Muzdalifah; Kusmanto , Indar; Hidayat, Hidayat (AhInstitute of Research and Community Service (LP2M) Institute of Social Sciences and Business Andi Sapada, 2024)
The aim of this research is to find out how to design and implement an Android-based educational game application to introduce culture and ethnicity in West Sulawesi which is expected to contribute to motivating students to get to know culture and ethnicity in West Sulawesi. This application or system was created using the Java and MySQL programming languages, where this application is used to facilitate learning that is full of modern education by following current technological developments. And based on the results of the implementation, it has been successful and has had an influence on motivation to learn about culture and ethnicity in West Sulawesi